The Colorimetry in “Heathers” - Donadio, Isaura Gurian (Revista do Colóquio, 2023)
"Heathers" (1988), directed by Michael Lehmann, is a dark comedy and teen drama that navigates the complexities of high school dynamics. This article explores the use of color in the film's cinematography, with a focus on visual storytelling. The analysis investigates the symbolism of the colors associated with each character, the transformation of the characters through changes in costumes and scenography. The film's use of color serves as a powerful visual storytelling tool, enhancing the audience's understanding of the characters and evolving themes within the narrative.